1994
DOI: 10.1677/joe.0.1400111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of somatotrophic function induced by deprivation of growth hormone-releasing hormone during the fetal life of the rat

Abstract: We have studied the effects of intra-amniotic administration of an anti-GH-releasing hormone serum (GHRH-Ab) on day 16 of fetal life in the rat, when the ontogenetic development of the GHRH neuronal system occurs. Control animals received normal rabbit serum. Following delivery, body weight was monitored for the next 30 days as an index of somatic growth, and the following indices of somatotrophic function were determined: plasma and pituitary GH, pituitary GH mRNA, hypothalamic GHRH and somatostatin mRNA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…However, in a previous study (1) we showed that in the rat passive immunization against GHRH during the early postnatal period has profound and long-term effects on subsequent somatic growth and somatotropic function. Partial pituitary dependence of growth, even at the earliest neonatal stage, has also been evidenced more recently (25)(26)(27). In the present study, the ability of GH replacement therapy to reverse some defective indices of somatotropic function in GHRH-deprived 10-d-old rats reinforces the view that somatic growth is pituitary dependent very early in the postnatal period.…”
Section: Discussionsupporting
confidence: 87%
“…However, in a previous study (1) we showed that in the rat passive immunization against GHRH during the early postnatal period has profound and long-term effects on subsequent somatic growth and somatotropic function. Partial pituitary dependence of growth, even at the earliest neonatal stage, has also been evidenced more recently (25)(26)(27). In the present study, the ability of GH replacement therapy to reverse some defective indices of somatotropic function in GHRH-deprived 10-d-old rats reinforces the view that somatic growth is pituitary dependent very early in the postnatal period.…”
Section: Discussionsupporting
confidence: 87%
“…For example, passive immunization of the fetal rat against growth hormone (GH)-releasing hormone permanently alters adult GH secretion (Cella et al 1994). Muaku et al (1996) showed in the rat that offspring from mothers fed on a low protein diet throughout gestation are growth retarded at birth and have reduced plasma levels of IGF-I postnatally until they reach puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of GHRH within the hypothalamus or GHRH action in the pituitary at a critical developmental window have a long lasting impact on body weight (Lin et al 1993, Robinson et al 1993, Cella et al 1994 and induce an inadequate clonal expansion of the somatotrope population. The requirement of GHRH for the normal development of the somatotrope lineage is evident from studies examining the etiology of growth retardation in the spontaneous mutant mouse, lit/lit, with a point mutation in the GHRH-R gene in which somatotropes fail to proliferate normally, resulting in a mature pituitary containing a limited number of GH cells (Lin et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of GHRH for the normal development of the somatotrope lineage is evident from studies examining the etiology of growth retardation in the spontaneous mutant mouse, lit/lit, with a point mutation in the GHRH-R gene in which somatotropes fail to proliferate normally, resulting in a mature pituitary containing a limited number of GH cells (Lin et al 1993). Likewise, an experimentally induced reduction of GHRH during the fetal period, by passive immunization with GHRH antiserum, results in growth retardation characterized by a decreased pituitary size and GH content (Cella et al 1994). In this respect, it has been shown that GHRH plays a major stimulatory role in the regulation of the Pit-1 mRNA concentration (Müller et al 1999), and in the direct regulation of pituitary GHRH-R mRNA and the GH gene.…”
Section: Discussionmentioning
confidence: 99%